Pengembangan Modul IPAS Berbasis PBL untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa MI - Aswah Julita; Boby Syefrinando (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This research is motivated because the teaching materials used are still conventional and students' understanding of problem solving is still in the low category. Therefore, this study aims to develop research and improve the validity, practicality and effectiveness of the Science learning module for Class V MI Muhajirin, Jambi City. Reach and Development (R&D) consists of four stages, namely, define, design, develop and disseminate. This type of research is Research and Development (R&D). This research was conducted at Madrasah Ibtidaiyah Al-Muhajirin, Jambi City. The instruments used were assessment questionnaires, teacher and student interview sheets along with test questions. The subjects in this study were grade V students consisting of 20 students. The results of this study indicate that the level of validity of the application of the learning module shows a percentage of 80% included in the very effective category, the level of practicality shows 92.8% with a very practical category and the level of effectiveness shows a percentage of 64.2% with a very valid category.